2020
DOI: 10.36708/littera_scripta2019/2/2
|View full text |Cite
|
Sign up to set email alerts
|

Structural Development of Utilised Agricultural Area in EU Countries Subsidy Policy of the Czech Republic

Abstract: In the introductory part the authors deal with the importance of agricultural land, its influence on water management, on the production of food for inhabitants, the utilization of land in agriculture, the influence on the climatic condition and the global ecosystem. They point out the problems related to the reduction of agricultural areas and they quote opinions of selected environmental specialists. They mention the issue of the subsidies in the Czech Republic, their sources and accounting. In the next part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In this regard, the current methodology does not appear to be fair (Junga et al, 2019). Kabourková and Stuchlý (2019) focused on the analysis of the progressive land acquisition for agricultural use in individual EU countries. They concluded that in the years 2007-2017, there was an overall decrease in the acreage of land used for agricultural production in the EU countries, with the largest decline in land use for agricultural production being recorded in Cyprus (by 2.03%) and Austria (by 1.97%).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this regard, the current methodology does not appear to be fair (Junga et al, 2019). Kabourková and Stuchlý (2019) focused on the analysis of the progressive land acquisition for agricultural use in individual EU countries. They concluded that in the years 2007-2017, there was an overall decrease in the acreage of land used for agricultural production in the EU countries, with the largest decline in land use for agricultural production being recorded in Cyprus (by 2.03%) and Austria (by 1.97%).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many experts closely link a green economy to a dependency of economic development from natural environmental factors [14][15][16][17][18]. Green economies initiate an implementation of new technologies that increase natural capital and decrease environmental risks [19][20][21].…”
Section: Introductionmentioning
confidence: 99%